The Sagittal Tibial Tubercle–Trochlear Groove Distance as a Measurement of Sagittal Imbalance in Patients with Symptomatic Patellofemoral Chondral Lesions. (December 2021) - Lansdown, Drew A.; Christian, David; Madden, Brett; Redondo, Michael; Farr, Jack; Cole, Brian J.; Yanke, Adam B.
Objective . To measure the sagittal alignment of the tibial tubercle through the sagittal tibial tubercle–trochlear groove (sTTTG) distance in patients with and without patellar chondral lesions. Design . Patients treated with patellofemoral cartilage restoration or repair procedures were retrospectively reviewed (group 1; N = 17). A control group of patients (group 2; N = 20) undergoing partial meniscectomy with normal patellar cartilage was included. An asymptomatic patellar chondrosis group (group 3; N = 15) was identified as patients undergoing partial meniscectomy with patellar cartilage wear. The sTTTG was measured on the preoperative axial T2 magnetic resonance imaging (MRI) sequence. The first point was the nadir of the anterior trochlear cartilage, and the second point was the anterior tibial tubercle. A line was drawn between these points, perpendicular to the posterior condylar axis. Comparisons were made between the 3 groups using analysis of variance testing with Bonferroni corrections. Significance was defined as P < 0.05. Results . The mean sTTTG was significantly more posterior in group 1 (5.9 ± 5.5 mm posterior to the trochlear groove) relative to group 2 (0.8 ± 5.3 mm posterior; P = 0.018). The mean value for group 3 (2.7 ± 5.3 mm posterior) fell between group 1 and 3 but was not significantly different from group 1 ( P = 0.31) or group 2 ( P = 0.89). There were no significant differences with regards to sulcus angle, Caton-Deschamps Index, TTTG, or knee flexion angle on the MRI scan. Conclusions . A more posteriorly positioned tibial tubercle was observed in patients with patellar cartilage lesions relative to those with intact patellar cartilage. Intermediate positioning was observed in patients with asymptomatic patellar chondral wear. Level of Evidence . Level 3 diagnostic study.